Tingkat Minat Siswa SMP Negeri 3 Yogyakarta terhadap Layanan Cybercounseling - Jinggoi Jinggoi; Bernadinus Agus Arswimba (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study aims to 1) Find out the level of interest of students at SMP Negeri 3 Yogyakarta for Cybercounseling services. 2) Measuring the achievement level of the score of interest items of interest for SMP Negeri 3 Yogyakarta students. This study uses an approach with a descriptive quantitative method. This study is aimed at students in grade IX of SMP N 3 Yoyakarta, the sample of this study is 130 students, data collection using the Interest Scale (58 items and all valid with a reliability test of 0.941). Data analysis used descriptive categorization techniques. The results of this study show that: 1) grade IX students of SMP N 3 Yogyakarta, have a moderate level of interest in cybercounseling services with a percentage of 62 (47.69%), and almost half of the total students, namely 59 (45.38%), who show interest in the high category. Meanwhile, the categories of students with very high, low, and very low interest were relatively small, at 3.85%, 2.85%, and 0.77%, respectively. 2) Identified The majority of the items statement in the interest scale, reaching 52 (89.66%), received a high response from the students. In addition, only 6 (10.34%) statements received a response at a moderate level.